Analisis Keterampilan Menyimak pada Siswa Kelas 3 melalui Media Gambar di MI Sultan Agung - Zuhrotun Nisah Maslahkatul Ummah; Nanang Khoirul Umam (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research was motivated by the low listening activities of elementary school students. Researchers conducted observations of learning activities with grade III elementary school students to determine their listenng skills, from the observation, the result showed that there were still students who had difficulty understanding the material, difficulty concentrating and easly bored with the activity of listening to the material being presented deductive and inductive paragraphs in Indonesian. This study aims to analyze the listening skills of elementary school students using learning media and aims to improve the concentration and understanding of grade III students during listening activities using learning media. This research using quantitative descriptive research methods, the research subjects of which are class III MI Sultan Agung. The results of this study show that students’ ability to listen to deductive and inductive paragraph material without using media is 55% while students’ ability to listen to deductive and inductive paragraph material using media is 100% with very good category. Meanwhile, students’ ability to identify deductive and inductive paragraphs in reading was 88% in the very good category.